Partisanship, Religion, and Social Class: Attitudes and Behaviors in the Early Stages of the Covid-19 Pandemic - Burhanuddin Muhtadi; Seth Soderborg (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
This article investigates differences in health precautions taken during the pandemic and the degree to which individuals had faith in the government’s response to Covid-19 in the early stages of the pandemic. Using a sample designed to be nationally representative as well as representative of three lockdown zones, we find that local social-distancing policies, social class, religion, and political partisanship all influenced how Indonesians experienced the pandemic and their perceptions of the government’s response. We found that fear levels and pandemic behavior are associated with religion as well as economic status. Fear levels are much higher among lowest-paid Indonesians and among Muslims outside of the capital city Jakarta, while non-Muslims reported greater levels of precaution-taking measures. Though among Islamic parties’ voters, the difference is less pronounced, there are notable partisan differences as stronger predictors of attitude and behavior during the pandemic where there have been conflicts between local and national health authorities.